The economic and labor impact of the 100 law on the licensed empiric dentist members of the Antioquia Dental Association - ASODENTA - Castro-N., Jaime; Correa-A., James; Gutiérrez, Luis; Cuartas-F., Luisa; Pérez-M., Juan (Revista Facultad de Odontología Universidad de Antioquia, 2018)
By 1993 was made the h:rst colambian health and sodal welfare amend, better Know as "Ley100". This- amend broke the old health service °utiliza The new interpretado.n ofhealth Jaws has affected the priva te medica] and odontologicalpractice. Medical income has been disminish su_stantrally, according to socia 1 investigators. Colombian Constitution allows some restricted odontological practicing to persons ha ving no academic preparation, but some empirical odontological Knowledge. According to the new regulations we want to measure how much are been laboraly- affected those licensed practica] dentists. It 1s Important to remernber that a considerable fraction of colombians prefer practica] dentist, since their cheaper bilis. We pretend essencially describe the consecuences of 100 law as a negative factor in empirical praciicing of dentist. As a second goal we assume a descriptive approach. We analize a sample of 85 licensed practica] dentists of Antioquia county "ASODENTA", whose consulting rooms are located in the cities of Medellín, Bello, Itagill and Envigado. Data colletion was using survey during a period of 4 months. In this study was found that patients who used to visit licensed practica] dentists diminished as a consecuence of 100 law. This situation led the licensed practica] dentist expermented non - sufficient incomes, laboral inestabiliT and also they felt the need to dedica te their laboral practice to other dentistry areas. Actually, they offer dental services out of POS to contrarrest that situation.